2020
DOI: 10.1002/lary.28893
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in N3 Head and Neck Squamous Cell Carcinoma and Role of Upfront Neck Dissection

Abstract: Objectives We investigated the prognostic factor of N3 head and neck squamous cell carcinoma (HNSCC), including the role of upfront neck dissection (UFND) before radiotherapy (RT). Methods We retrospectively reviewed the charts of consecutive N3 HNSCC patients treated with curative intent RT. Results In the study, 323 N3 HNSCC patients were included. Of those, 125 patients (39%) had UFND. Median follow‐up was 3.9 years (0–14.8 years). Overall survival (OS) at 5 years was 31.2%, and progression‐free survival (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the upfront ND group showed a signi cant trend towards better DSS and OS outcomes. Carsuzaa et al [19] reported that upfront ND signi cantly improved locoregional control and Boros et al [17] reported that upfront ND could be associated with improved outcomes in non-oropharyngeal N3 HNSCC. In this study, DFS in the CRT group was slightly worse than that reported [12,17], and the results declined rapidly over two years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the upfront ND group showed a signi cant trend towards better DSS and OS outcomes. Carsuzaa et al [19] reported that upfront ND signi cantly improved locoregional control and Boros et al [17] reported that upfront ND could be associated with improved outcomes in non-oropharyngeal N3 HNSCC. In this study, DFS in the CRT group was slightly worse than that reported [12,17], and the results declined rapidly over two years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the clinical outcomes and overall prognosis of N3 cases with extranodal extension are poor [15]. One approach for improving cervical lymph node control rates is upfront neck dissection (ND) before CRT [5,16,17]. However, evidence regarding its impact on prognosis is con icting, with some studies showing improved outcomes [17,18] and others suggesting no signi cant improvements [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…36 Performing an initial ND approach might be a strategy to control regional disease by removing necrotic or hypoxic bulky neck nodes before CTX-RT. 37 Nevertheless, regional and distant progression can still occur in these patients, suggesting that metastatic potential is intrinsic to the initial nodal stage. Furthermore, in patients with resectable N3 (AJCC 7th) disease, ND has improved locoregional control but implies surgical morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, prognostic factors for locoregional relapse, PFS and HNCUP-specific death included an interval of more than 10 weeks between diagnosis and radiotherapy. In head and neck cancers, the longer the delay between initial surgery and adjuvant radiotherapy, the shorter the survival [ 28 , 29 , 30 ]. The PET-CT prognostic value for HNCUP-specific in our study probably indicated better detection of synchronous metastatic lesions [ 11 , 19 , 29 , 31 , 32 , 33 ] (and further exclusion of these patients from our studies).…”
Section: Discussionmentioning
confidence: 99%